La Monterita Canela (Poospiza ornata) en la provincia de Entre Ríos, Argentina - Roesler, Ignacio; Povedano, Hernán; Di Giacomo, Adrián S.; Spitznagel, Oscar (Nuestras Aves, 2006)
Este artículo no cuenta con un resumen.